2008
DOI: 10.2741/3127
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic biomarkers for human cancer

Abstract: Human cancer cytogenetics is the study of chromosomal rearrangements and numerical abnormalities in malignant tissue. Since the 1960s and the discovery of the Philadelphia chromosome, hundreds of common and characteristic chromosomal aberrations have been observed in various neoplasias. Because these cytogenetic aberrations provide diagnostic, prognostic, and treatment-related information for the associated cancers, they are considered biomarkers for disease. Here we describe many of the best-known chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 80 publications
(126 reference statements)
0
23
0
Order By: Relevance
“…[1] These aberrations are not always shared by cells of the same tumor and may not necessarily linked to a particular tumor type. [2] It was Theodor Boveri who first observed that cells with supernumerary centromeres missegregated their chromosomes through the assembly of multipolar spindles and hypothesized that those abnormal chromosomes might contribute towards carcinogenesis. [3] Micronuclei has been used as a measurement and bio monitoring of genotoxicity of various carcinogens, heavy metal poisoning, antineoplastic drugs, pollutants etc., In last few decades it has been used as a biomarker of chromosomal damage, genome instability and cancer risk.…”
Section: Introductionmentioning
confidence: 98%
“…[1] These aberrations are not always shared by cells of the same tumor and may not necessarily linked to a particular tumor type. [2] It was Theodor Boveri who first observed that cells with supernumerary centromeres missegregated their chromosomes through the assembly of multipolar spindles and hypothesized that those abnormal chromosomes might contribute towards carcinogenesis. [3] Micronuclei has been used as a measurement and bio monitoring of genotoxicity of various carcinogens, heavy metal poisoning, antineoplastic drugs, pollutants etc., In last few decades it has been used as a biomarker of chromosomal damage, genome instability and cancer risk.…”
Section: Introductionmentioning
confidence: 98%
“…Chromosomal abnormalities are a hallmark of cancer, with numerous examples of non-random translocations found in leukaemia [1,2]. Recurrent chromosomal abnormalities are used in the clinical practice for their diagnostic and prognostic value, their association with specific subtypes and subsequently as parameters on which to base therapy decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Homologous recombination (HR) is a fundamental DNA repair pathway and its deregulation is responsible for a variety of genomic rearrangements, including chromosome loss, DNA translocations and inversions, which are typical of the genetic alterations seen in tumor cells (reviewed in [1]). The mechanisms and proteins involved in HR have been well conserved throughout evolution and much of our knowledge on HR comes from studies conducted in the yeast Saccharomyces cerevisiae (reviewed in [2]–[5]).…”
Section: Introductionmentioning
confidence: 99%